Multikodalität und Digitales Lehren und Lernen - Ersch, Christina Maria; Grein, Marion (DaF / DaZ in Forschung und Lehre, 2021)
Nothing has highlighted the importance of digital teaching and learning opportunities more obviously than the Corona pandemic. This book therefore focuses on multicodal or multimedia digital teaching. The authors examine it from various perspectives and make suggestions for successful didactic implementation. In addition to general topics of digital teaching, they devote particular attention to visual literacy, which plays a special role in multimedia teaching. Criticism of teachers' lack of digital skills alone will not lead to success. Therefore, ways are shown here how these skills can be acquired. Tips and concrete examples for suitable apps, serious games, and online training courses round off the volume. Christina Maria Ersch is a staff member/DaF coordinator at the International Office of the University of Applied Sciences Mainz and lecturer at the University of Mainz. Her research interests lie in (university) didactics, especially in the implementation of competence orientation and digitalization of teaching of teaching, intercultural communication, and the influence of emotions in of emotions in (foreign language) teaching. Dr. Marion Grein is head of the Master's program DaF/DaZ at the the University of Mainz. Her work focuses on language teaching research (neurodidactics), intercultural communication, and digital teaching.